Optimization of Character Education Through Community Participation Around The School Environment (Case Study in Lab School Junior High School Bandung) - Jagad Aditya Dewantara; Efriani Efriani; Sulistyarini Sulistyarini; Wibowo Heru Prasetiyo (Universitas of Muhammadiyah Makassar, 2020)
The community environment has an essential impact on the formation of student character in schools. Therefore, character education is a crucial step in shaping the identity of the Indonesian people. This study aims to determine the optimization of character education through community participation around the school environment at Junior High School Lab School Bandung. This research method uses a case study centered on Bandung Lab school Middle School. The results showed that the character education conducted at Lab school Junior High School Bandung could run well because of the collaboration between the school and community participation around the school environment. The partnership carried out produces values that help build student character. The values include religious values, integrity values, nationalist values, independent values, and mutual values.Keywords: Character Education, Community Participation, The Environment Around the SchoolLingkungan masyarakat memiliki dampak yang penting bagi terbentuknya karakter siswa di sekolah. Oleh karena itu, Pendidikan karakter merupakan langkah sangat penting dalam membentuk jati diri bangsa Indonesia. Penelitian ini bertujuan untuk mengetahui optimalisasi pendidikan karakter melalui partisipasi masyarakat sekitar lingkungan sekolah pada Sekolah Menengah Pertama Labschool Bandung. Metode penelitian ini menggunakan studi kasus yang berpusat pada Sekolah Menengah Pertama Labschool Bandung. Hasil penelitian menunjukkan bahwa pendidikaan karakter yang dilakukan pada Sekolah Menengah Pertama Labschool Bandung dapat berjalan dengan baik karena kerjasama antara sekolah dan partisipasi masyarakat sekitar lingkungan sekolah. Kerja sama yang dilakuan menghasilkan nilai-nilai yang turut membangun karakter siswa. Adapun nilai-nilai tersebut meliputi Nilai religius, Nilai integritas, Nilai nasionalis, Nilai mandiri dan Nilai gotong-royong.Kata Kunci: Pendidikan Karakter, Partisipasi Masyarakat, Lingkungan sekitar Sekolah